Clinical safety of amino acids and vitamins administered through parenteral route - Alessandra Cristina de Moraes; Marcos Roberto Scherma; Ed Johnny da Rosa Prado; Vanessa Pavesi de Faria; Ives Charlie da Silva; Wilson Gomez Manrique; Marco Antonio de Andrade Belo (International Journal of Veterinary Science and Research - Peertechz Publications, 2017)
The parenteral use of amino acids and vitamins has been used to improve performance in animal  production. However, few studies demonstrating the toxicity of these compounds. The present investigation evaluated the toxicological and clinical safety of the injectable supplement compound by amino acids and vitamins, administered by intramuscular route in Wistar rats. 56 females (± 220g), pubescent virgins, were randomly divided into seven groups (n=8): Treated with dose of 0.2, 2 and 4 mL,sampled 24 and 96 hours post-treatment (HPT), totaling six groups and one control group (Physiology Standard). Signifi cant increase in the enzymatic activity of serum ALT, AST, LDH and ALP was observed in animals treated with 2 and 4 mL (24 HPT). However, these changes returned to baseline levels 96 HPT, except in serum AST and ALP in animals treated with 4 mL. CK-NAC showed dose-response effect,since the higher compound dose was followed by proportional increase in the circulating levels of this enzyme, associated to muscle degeneration and necrosis area in rats treat with 4mL at 96 HPT. The evaluation of hepatic function did not result in signifi cant changes in the serum levels of triglycerides,cholesterol, albumin, urea and creatinine in the comparison between rats treated with 0.2 mL and control rats, demonstrating the innocuousness of this treatment on the activity of liver and kidney. However,deleterious effects were observed in animals subjected to doses of 2 and 4 mL, including observed increased splenic and hepatosomatic response, signifi cant decrease in circulating albumin levels and signifi cant leukocytosis, which is characterized by neutrophilia, followed by lymphopenia demonstrating the compound irritating effect on muscle tissue.